Compilation and Distribution of Mineral Resource Information in the United States - Davidson, David F. (Journal of Information and Knowledge, 1978)
The general problems encountered and the products emanating from Mineral Information Systems, including computer-based storage and retrieval systems, are discussed. A brief description of the major computer-based information systems, such as, Rock Analysis Storage System (RASS), Computerized Resource Information Bank (CRIB), Minerals Availability System (MAS) is given.